SOME NEW REMARKS ON POWER SUMS - Casinillo, Leomarich F (Diponegoro University, 2022)
Power sum is one of the interesting topics in number theory where its application in other sciences is known to be wide. This paper intends to stipulate new remarks on an explicit polynomial solution to power sums. Additionally, it investigates the general solution under odd and even numbers of terms and discusses some examples.